4(x-3)+6(x+10)-15=-23

Simple and best practice solution for 4(x-3)+6(x+10)-15=-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-3)+6(x+10)-15=-23 equation:


Simplifying
4(x + -3) + 6(x + 10) + -15 = -23

Reorder the terms:
4(-3 + x) + 6(x + 10) + -15 = -23
(-3 * 4 + x * 4) + 6(x + 10) + -15 = -23
(-12 + 4x) + 6(x + 10) + -15 = -23

Reorder the terms:
-12 + 4x + 6(10 + x) + -15 = -23
-12 + 4x + (10 * 6 + x * 6) + -15 = -23
-12 + 4x + (60 + 6x) + -15 = -23

Reorder the terms:
-12 + 60 + -15 + 4x + 6x = -23

Combine like terms: -12 + 60 = 48
48 + -15 + 4x + 6x = -23

Combine like terms: 48 + -15 = 33
33 + 4x + 6x = -23

Combine like terms: 4x + 6x = 10x
33 + 10x = -23

Solving
33 + 10x = -23

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-33' to each side of the equation.
33 + -33 + 10x = -23 + -33

Combine like terms: 33 + -33 = 0
0 + 10x = -23 + -33
10x = -23 + -33

Combine like terms: -23 + -33 = -56
10x = -56

Divide each side by '10'.
x = -5.6

Simplifying
x = -5.6

See similar equations:

| 3x(3x^2-10x+3)=0 | | -12h=-60 | | 42=144 | | X+y=4z | | 3x^2+18+24= | | 2a+4=12a+6 | | a*a(a-2b)+3b(a*a-4)= | | t+15=20 | | =-4x^3+18x | | 1/3n4 | | -2p+1=5 | | (5x+7)-(3x-1)=22 | | 2x^2-6ix^3-2x^2+(3-4i)x-5i+2=0 | | 2x^2-6ix^3-2x^2+(3-4i)x-5i=0 | | 2x^2+5x+3=15 | | 22x^2+5x+3=15 | | 0.5x+2.49=-.07x+6.69 | | 1=b-13 | | 3cos^2x=7sinx+5 | | X-52=100 | | 7x+9y=107 | | 2-3x=-2-2x | | 8-1/4z=1 | | 3,6*4/0,6*8 | | 6v=198 | | 4(x+5)-24=5x-13 | | 13+n=23 | | 25=a/b | | 15=2x+5x+3 | | (10w-9)(8w+7)= | | 2x^4-8x-3=0 | | 4y+5(5-y)-20+2y= |

Equations solver categories